Dyschromatosis symmetrica hereditaria - K. Geetha (Journal of Clinical and Scientific Research)
Dyschromatosis symmetrica hereditaria (DSH) is an autosomal dominant pigmentary genodermatosis characterised by a mixture of hyperpigmented and hypopigmented macules on the dorsal aspects of the hands and feet. The majority of cases of this condition have been reported in East Asian countries such as Japan, China and Taiwan. The gene responsible for DSH has been identified as adenosine deaminase acting on ribonucleic acid1 (ADAR1). To date, more than 100 ADAR1 mutations have been reported in DSH patients, and the catalytic domain deaminase is thought to be critical to the gene’s activities. We report a case of DSH, a rare cutaneous disease with classic clinical manifestations and a family history of similar illness. The skin lesions were characterised by a mixture of hyperpigmented and hypopigmented macules and were localised on the dorsum of the hands and feet of three persons of the same family.